The urban population and Nazi propaganda during the World War II (on the example of the cities of Zhytomyr region) - Stelnikovich, Sergey (City and War, 2021)
The population of the Nazi-occupied territory of Ukraine was systematically influenced by propaganda. Nazi propaganda was aimed at the urban population of the Zhytomyr region. Zhytomyr region occupied one of the central places in the occupation policy of Germany. Heinrich Himmler’s quarter was located near Zhytomyr, and the German colonies Hegewald and Forsterstadt were established here. Zhytomyr region had a multi-ethnic population and was active in the resistance movement. Newspapers, radio, newsreels, and leaflets were the main means of Nazi propaganda among the urban population of the Zhytomyr region. The Nazis carried out anti-Soviet propaganda among the population of the region’s cities. This propaganda was carried out by such methods as the destruction of monuments and changing the names of individual settlements. Streets, squares and alleys began to change in cities. In the second half of 1943 the main method of propaganda was the exhumation of the victims of the Vinnytsia NKVD. Anti-Jewish propaganda occupied a special place. The reason is that some cities in the Zhytomyr region, including Berdychiv, were centers of Jewish culture in the pre-war period. Anti-Jewish propaganda was systemic in nature and combined with anti- -Soviet propaganda campaigns. An important direction of Nazi propaganda during the World War II among the urban population of the region were campaigns aimed at supporting the occupation policy and the occupation order.